2009
DOI: 10.1002/jmv.21610
|View full text |Cite
|
Sign up to set email alerts
|

Viral causes of influenza‐like illness: Insight from a study during the winters 2004–2007

Abstract: Limited information is available on the viral etiology of influenza-like illness in southern European countries, and it is still a matter of debate whether certain symptoms can be used to distinguish among the specific viruses that cause influenza-like illness. The main objective of the present study was to identify the demographic and clinical predictors of influenza-like illness due to specific viral agents. The study, which was observational in design, was conducted in Rome and Naples, Italy. Cases of influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 21 publications
10
31
4
Order By: Relevance
“…Concerning the clinical presentations of influenza virus infections fever (88.5%) and cough (84.6%) were the most common presenting symptoms followed by Rhinorrhra (76.9%) and whereas GIT symptoms appeared as uncommon clinical finding (7.7%). This was in agreement with Puzelli et al [26] & Ohmit and Monto [28] who reported that fever and cough are the best predictors for influenza virus infections. Fifteen (57.7%) of positive cases for influenza virus infection occurred in winter with peak in January 2011 [16,26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning the clinical presentations of influenza virus infections fever (88.5%) and cough (84.6%) were the most common presenting symptoms followed by Rhinorrhra (76.9%) and whereas GIT symptoms appeared as uncommon clinical finding (7.7%). This was in agreement with Puzelli et al [26] & Ohmit and Monto [28] who reported that fever and cough are the best predictors for influenza virus infections. Fifteen (57.7%) of positive cases for influenza virus infection occurred in winter with peak in January 2011 [16,26].…”
Section: Discussionsupporting
confidence: 92%
“…This may be attributed to that school-age children have the highest contact rates and they have less immunity to influenza than adults and tend to excrete large amounts of virus. Another explanation of this age distribution is the higher vaccination coverage among older adults or the duration of viral shedding in young children which is usually longer than in adults and characterized by higher virus concentration [26]. Also sample collection may be more difficult in adults than in children since adults may resist more strongly the taking of swabs or blow their noses more often and thereby reduce the quantity of virus in the nasopharyngeal swab [27].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with ARI, muscle/joint pain was associated with influenza A, whereas headache was positively associated with influenza B. One previous study by Puzelli and others 13 demonstrated the similar association between muscle/joint pains and headache and influenza infection. However, another study by Yang X and others, Beijing failed to demonstrate that muscle/joint pains or headache were associated with influenza virus.…”
Section: 10mentioning
confidence: 63%
“…First of all, the identification of the cause of ARI remains challenging, due either to inadequate samples that may lead to false negative results, or to difficult interpretation of positive findings between infection and colonization. Secondly, the low proportion of cases attributable to influenza viruses might be explained by the place of recruitment, since influenza is usually underrepresented in hospital-based studies [14]. In a previous study conducted in the same site, the respiratory syncytial virus was detected in 7% of the samples, representing 8% of all isolates, compared with 5% for influenza [9].…”
Section: Discussionmentioning
confidence: 99%